Pengaruh Identitas Tempat, Pemerekan Tempat Terhadap Citra Tempat Melalui Event The 18th Jakarta International Handicraft Trade Fair 2016 - Michael Christian (Jurnal Hospitality dan Pariwisata, 2017)
Nowadays, the sector of tourism is aimed to contribute siginificantly for the national gaincompared to other sectors in Indonesia. One of the most promising things on that sector isevent. Jakarta as the capital city of Indonesia becomes the pulse of showing the small eventto the international scale. Jakarta International Handicraft Trade Fair (INACRAFT) is oneof the international scale of event which contains the identity of handicraft in Indonesia.Enjoy Jakarta as the brand of Jakarta has been increasing its branding through the qualifiedplaces in Jakarta in order to make Jakarta as the city of event. This research aims to find theimpact of the place identity, place branding towards to place image. This quantitative methodwhich invloved 45 visitors of INACRAT results that variables impacts the independentvariable partially and simultaneouly. Next researches are suggested to use other subject suchas food festivals, the beauty contests, and the sport events in order to enrich the resultthorugh the other unique events.Keywords: place identity, place brand, place image, INACRAFT